2014
DOI: 10.5296/ijld.v4i1.5010
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback Interventions and EFL Learners’ Pronunciation: A Case of –s or –es Ending Words

Abstract: This quasi-experimental study aimed to investigate the impact of two corrective feedback techniques (recasts and prompts) on students' performance in pronunciation. Seventy-two students from SAMA High School in Ardabil were assigned as the participants of this study. The data were collected from 3 classroom-based studies; the two experimental conditions -one received corrective feedback in the form of recasts and the other in the form of prompts -and a control group. The instructional intervention, which was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Therefore, feedback on pronunciation is as important as feedback on other components of communicative competence (Bachman & Palmer 2009; Common European Framework of Reference for Languages 2001) because students need to learn how to speak intelligibly to others (Zielinski & Yates 2014). As stated earlier, several studies have shown the positive impact of feedback on oral accuracy (Dlaska & Krekeler 2013;Mohammadi Darabad 2014;Saito & Lyster 2012).…”
Section: Teacher Feedback On Writing Compared To Pronunciation In Catmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, feedback on pronunciation is as important as feedback on other components of communicative competence (Bachman & Palmer 2009; Common European Framework of Reference for Languages 2001) because students need to learn how to speak intelligibly to others (Zielinski & Yates 2014). As stated earlier, several studies have shown the positive impact of feedback on oral accuracy (Dlaska & Krekeler 2013;Mohammadi Darabad 2014;Saito & Lyster 2012).…”
Section: Teacher Feedback On Writing Compared To Pronunciation In Catmentioning
confidence: 92%
“…Language accuracy in the present study involves feedback both in a written context (grammar, lexis and spelling) as well as on pronunciation, i.e., oral accuracy. It is noteworthy that several recent studies have shown the relative effectiveness of explicit feedback on pronunciation, and suggest that feedback on pronunciation is vital for successful pronunciation (Dlaska & Krekeler 2013;Mohammadi Darabad 2014;Saito & Lyster 2012). Learners do not always hear their pronunciation mistakes and need to be taught and scaffolded with feedback (Zielinski & Yates 2014).…”
Section: The Productmentioning
confidence: 99%
“…Consequently, providing OCF has positive contributions to the pronunciation uptake of learners and OCF seems to be more beneficial for pronunciation than it is for other language areas. Comparing the effects of two OCF techniques, namely recasts and prompts, on students' pronunciation of the final -s and -es endings in an Iranian EFL context, Darabad (2014) revealed a positive effect of such an intervention, with recasts having a greater impact than prompts. In a different context, Gooch, Saito and Lyster (2016) compared the effects of recasts, prompts and no feedback on Korean EFL learners' pronunciation development of an English consonant in a form-focused instruction.…”
Section: Oral Corrective Feedback and L2 Pronunciationmentioning
confidence: 97%
“…In the literature, research has focused on the effects of different OCF forms (e.g. Darabad, 2014;Saito & Lyster, 2012a) and techniques (e.g. Gooch, Saito & Lyster, 2016;Luquin & Roothooft, 2019) on pronunciation, the effect of OCF on learner uptake in pronunciation in particular (Lee, 2016) and learners' perceptions of OCF (e.g.…”
Section: Oral Corrective Feedback and L2 Pronunciationmentioning
confidence: 99%
“…According to many scholars CF has an effective role in helping learners to notice their process of acquisition and therefore it is conductive to second language learning (Mackey &Philp, 1998;Philp, 2003;Sheen, 2007;Trofimovich,Ammar, & Gatbonton, 2007) A growing number of studies have worked on the effectiveness of different types of corrective feedback in both laboratory and classroom contexts (e.g. Lyster & Ranta, 1997;Ammar & Spada, 2006;Ellis, Loewen, & Erlam, 2006;Lyster & Izquierdo, 2009;Yang & Lyster, 2010;MohammadiDarabad, 2014). However, considering some other important factors related to the best time for having an effective CF process has remain to examine.…”
Section: Introductionmentioning
confidence: 99%